Giant Gastroschisis with Complete Liver Herniation: A Case Report of Two Patients - Wendy Jo Svetanoff; Benjamin Zendejas; Farokh R. Demehri; Alex Cuenca; Bharath Nath; C. Jason Smithers (Case Reports in Surgery)
Introduction. There are no reported survivors of gastroschisis with complete liver herniation. We describe a case report of two patients, one of whom survived. Case #1. The patient was born with gastroschisis and herniation of the entire liver. Along with silo placement, the abdominal fascia was attached to an external traction system for growth. Complete closure was achieved at 5 months. Due to pulmonary hypoplasia, high-frequency ventilation was required. The patient is doing well, on a home ventilator wean, at 20 months. Case #2. The patient was born prematurely with gastroschisis, total liver herniation, and a defect extending to the pericardium. A silo was attached to the fascia to provide growth of the abdominal cavity. The patient developed respiratory failure, diffuse anasarca, and renal failure. She died at 38 days of life. Discussion. We report the first survivor of gastroschisis with complete liver herniation, contrasting it with a death of a similar case. The associated pulmonary hypoplasia may require long-term ventilation, the inflammatory response can lead to anasarca, and renal injury can occur from acute-on-chronic compartment syndrome. Conclusion. External fascial traction systems can help induce growth of the abdominal wall, allowing closure of the challenging abdomen. While critical care management is complex, survival is possible.